Evaluation of the effects of group psychotherapy on cognitive function in patients with multiple sclerosis with cognitive dysfunction and depression - Bilgi, Emine; Ozdemir, Hasan Huseyin; Bingol, Ayhan; Bulut, Serpil (Assoc Arquivos Neuro- Psiquiatria, 2015)
Objective: This study will evaluate how decreasing depression severity via group psychotherapy affects the cognitive function of patients with multiple sclerosis (MS) who are also diagnosed with depression and cognitive dysfunction. Method: MS patients completed the Brief Repeatable Battery of Neuropsychological Tests and Beck Depression Inventory (BDI). The group members diagnosed with depression and cognitive dysfunction underwent group psychotherapy for 3 months. Upon completion of psychotherapy, both tests were readministered. Results: Depression and cognitive dysfunction were comorbid in 15 (13.9%) of patients. Although improvement was detected at the end of the 3-month group psychotherapy intervention, it was limited to the BDI and the Paced Auditory Test. Conclusion: Group psychotherapy might decrease cognitive impairment in MS patients.
Avaliação do efeito da psicoterapia de grupo sobre as funções cognitivas de pacientes com esclerose múltipla que apresentam simultaneamente alterações cognitivas e depressão
Keywords: multiple sclerosis; group psychotherapy; cognitive functions; cognitive dysfunction; depression